Effect of storage condition on the viability of sago effluents as carbon source in fermentation medium for bioethanol production - Mohamad Zulhisyam, Rashid; Dayang Salwani, Awang Adeni; Muhammad Norhelmi, Ahmad (Malaysian Society for Molecular Biology and Biotechnology (MSMBB), 2024)
In Sarawak, Malaysia, approximately 237 tons/day of sago effluent is commonly discharged into nearby river due to the sago starch extraction process. Due to the high concentration of polymeric compounds, particularly starch, in sago wastewater, which petrifies easily, this condition severely pollutes the environment in the affected area. This study was conducted to determine the viability of using sago effluent as a carbon source and fermentation medium for bioethanol production which indirectly help to minimize the environmental impact as well as the economics of the sago industry. The sago effluent obtained from the local sago mill was analysed for starch content and pH profile while stored at room and cold (4°C) temperature facility. Enzymatic hydrolysis was conducted to convert the residual starch into glucose as carbon source for bioethanol fermentation. Fresh sago effluent can be stored for up to 5 days in cold temperature where the starch content remains constant. The highest starch concentration in sago effluent was 61.33 g/L, in which 50.57 g/L glucose was obtained through the enzymatic hydrolysis process. Hence 82.5% of the starch to glucose conversion yield is revealed. Then, the sago effluent hydrolysate which acts as a carbon source as well as a fermentation medium able to generate 23.14 g/L of bioethanol, displays a 91% theoretical yield of glucose to ethanol. In conclusion, the utilization of sago wastewater as feasible alternative to cheap and locally available and sustainable source of raw materials to produce bioethanol.